ANALISIS MANAJEMEN RISIKO DALAM PENGELOLAAN PIUTANG SEBAGAI UPAYA UNTUK MEMINIMALISIR JUMLAH TUNGGAKAN PADA PT PLN (PERSERO) ULP TANDES - Rochmawati, Reni; Sinorowenti, Adelia Ayu; Milad, Mohammad Khusnu (Relawan Jurnal Indonesia, 2025)
Accounts receivable arrears are one of the problems that can disrupt the company's cash flow and financial performance, including at PT PLN (Persero) ULP Tandes. This study aims to analyze the application of risk management in managing receivables as an effort to minimize the amount of arrears of receivables at PT PLN (Persero) ULP Tandes. The method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. This research uses the COSO framework which consists of five main components, namely the control environment, risk assessment, control activities, information and communication, and monitoring. The results show that the majority of arrears come from household customers who have low payment awareness. PLN implements a receivables management strategy through sending invoices, WhatsApp Blast, MCB disconnection, and installation demolition. In addition, the use of ITO and EIS information systems supports the effectiveness of monitoring and controlling receivables. The implementation of COSO-based risk management is proven to be able to help companies minimize the risk of arrears and maintain the stability of operational cash flow.